Banking on Europe - Hodson, Dermot; Howarth, David; Spielberger, Lukas; Mugnai, Iacopo (Oxford University Press, 2026)
The European Union (EU)’s small, balanced budget is commonly considered to be one of the most important constraints on the Union’s powers. However, the EU has always borrowed, and it is now borrowing on the scale of a large state to aid member states’ economic recovery from the COVID-19 pandemic and to support Ukraine’s wartime economy. This book tells the story of how the EU became a sovereign-style borrower from Jean Monnet’s ‘American Loan’ in 1954 to the operation of the Recovery and Resilience Facility seven decades later. Drawing on archival analysis and elite interviews, it charts the origins and evolution of the European Commission, the European Investment Bank, the European Bank for Reconstruction and Development, and the European Stability Mechanism as European-level borrowers and asks how these bodies’ accountability to parliaments, auditors, citizens, and civil society groups can be improved. Borrowing is not simply a technocratic issue, but one that raises fundamental questions about what sort of polity the EU is and how it could develop in the future.